2010
DOI: 10.1007/s11095-010-0197-4
|View full text |Cite
|
Sign up to set email alerts
|

Bisethylnorspermine Lipopolyamine as Potential Delivery Vector for Combination Drug/Gene Anticancer Therapies

Abstract: Purpose To design novel synthetic gene delivery system in which the carrier molecule functions dually as a carrier and a cytotoxic agent targeting dysregulated polyamine metabolism in cancer. Methods Bisethylnorspermine (BENSpm) lipopolyamine was synthesized and its toxicity evaluated by MTS assay in MCF-7 and MCF-10A cells. Transfection activity was determined using luciferase plasmid DNA. Results Asymmetrical lipid analogue of polyamine anticancer drug BENSpm was synthesized using nucleophilic ring openi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…The 1 H NMR and 13 C NMR of compound 10 were found to agree with the known NMR spectra of 3,7,11-tri-Boc BSP reported in our previous study. 8 This result confirmed that the location of BSP substitution in LS-BSP shown Figure 1 and Scheme 2 is correct. We have also attempted synthesis of LS-BSP by reaction of 8 with 10 , but this approach failed due to decomposition of compound 9 during Boc deprotection with TFA.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The 1 H NMR and 13 C NMR of compound 10 were found to agree with the known NMR spectra of 3,7,11-tri-Boc BSP reported in our previous study. 8 This result confirmed that the location of BSP substitution in LS-BSP shown Figure 1 and Scheme 2 is correct. We have also attempted synthesis of LS-BSP by reaction of 8 with 10 , but this approach failed due to decomposition of compound 9 during Boc deprotection with TFA.…”
Section: Resultssupporting
confidence: 71%
“…7 We have recently proposed dually functioning cationic gene delivery vectors based on a class of drugs called polyamine analogues. 8 These agents exploit the self-regulatory nature of the metabolism of cellular polyamines and have multiple targets in the polyamine pathway. Polyamine metabolism is frequently dysregulated in cancer and other hyper-proliferative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…By devising systems capable of simultaneous CXCR4 inhibition and delivery of antitumor agents, it should be possible to improve the overall anticancer activity (26). As part of our long-term efforts to develop dually functioning polycations for combination drug/gene delivery (27, 28), we have recently reported synthesis of polycations based on a bicyclam CXCR4 antagonist Plerixafor (PAMD) (29, 30). The PAMD polymers showed dual functionality as efficient gene delivery vectors and CXCR4 antagonists that inhibited invasion of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Serum usually has a negative effect on in vitro transfection activity due to the interaction of positively charged polyplexes with serum proteins like albumin. 3537 Here the influence of serum on transfection of RPC/1.8 polyplexes was not as significant as the negative effect observed for RPC/3 and RPC/2 polyplexes, especially when the polyplexes were prepared at high w/w ratio. In MDAMB-231 cells, the transfection activity of the RPC polymers was not as high as in B16F10 cells.…”
Section: Resultsmentioning
confidence: 97%